A silver on 2D white-C3N4 support photocatalyst for mechanistic insights: synergetic utilization of plasmonic effect for solar hydrogen evolution. Issue 113 (28th November 2016) - Yi, Jianjian; She, Xiaojie; Song, Yanhua; Xu, Hui; Zhang, Peng; Mo, Zhao; Liu, Liang; Du, Daolin; Li, Huaming
Abstract : The photocatalytic activity of Ag/2D white-C3 N4 is enhanced via synergetic utilization of plasma effects from Ag and visible-light excitation of the semiconductor. Abstract : A photocatalyst integrating silver surface plasmon effect into two-dimensional g-C3 N4 nanosheets (2D white-C3 N4 ) was prepared successfully. The crystal structure, chemical states, morphology and photocatalytic performance of the prepared samples were researched by the comprehensive characterization methods. The photocatalytic activities of Ag/2D white g-C3 N4 composites were dramatically enhanced under visible light irradiation. When Ag content was optimized, 2% Ag/white g-C3 N4 exhibited the best photocatalytic activity. The electrochemical investigation verified the role of the hot electrons from the plasmonic Ag in the photocatalytic reaction. The plasmonic hot electron injection and advantages of 2D ultrathin structure improved the density of the electrons with reducibility and led to more efficient separation of photogenerated electron and hole pairs. The photocatalytic mechanism was also researched in detail via ESR analysis.